Financial Sector Regulation and the Revolving Door in US Commercial banks - Joël Cariolle; Elise S. Brezis (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
IntroductionThe "revolving door" is a practice quite widely in use in the United States, in which heads of state agencies, after completing their bureaucratic terms, are entering the very sector they have regulated. This phenomenon is also frequent in France, where it is coined "pantouflage", and in Japan, coined "amakudari" (descent from heaven). Research conducted and data collected by the research group Corporate Europe Observatory strongly suggest that this process is also significant within EU institutions.[1]In the last two decades, the revolving door and the intertwining relations between governments and private groups have intensified. The revolving door became so widespread in the financial sector that it has been pointed out by the OECD (2009) and NGO's (Transparency International-UK, 2011) as a major cause of the 2008 financial crisis. In its 2009 report on the revolving door and the financial crisis, the OECD therefore stressed the necessity to set appropriate rules and procedures to control conflicts of interest generated by this phenomenon (OECD, 2009).[2]The revolving door affects the economy through two main channels: a positive one as well as a negative one. On the one hand, this movement of individuals between the public and private sectors may lead to some positive effects and can be desirable. Indeed, the revolving door allows recruiting qualified bureaucrats, and the knowledge the bureaucrat has accumulated while working in the public sector is put in use in their future position. .../... [1] See http://corporateeurope.org/revolvingdoorwatch.[2] See also www.opensecrets.org. on the revolving door inside the US financial sector. See also Transparency International-UK (2011) and Transparency International (2010), which lay down the negative as well as positive effects of the Revolving door.
Keywords: D7; K2; K4; L1; L2; L5; 330